2011
DOI: 10.1002/pro.2003
|View full text |Cite
|
Sign up to set email alerts
|

Structural basis for extracellular interactions between calcitonin receptor‐like receptor and receptor activity‐modifying protein 2 for adrenomedullin‐specific binding

Abstract: The calcitonin receptor-like receptor (CRLR), a class B GPCR, forms a heterodimer with receptor activity-modifying protein 2 (RAMP2), and serves as the adrenomedullin (AM) receptor to control neovascularization, while CRLR and RAMP1 form the calcitonin gene-related peptide (CGRP) receptor. Here, we report the crystal structures of the RAMP2 extracellular domain alone and in the complex with the CRLR extracellular domain. The CRLR-RAMP2 complex exhibits several intermolecular interactions that were not observed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
70
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 55 publications
(75 citation statements)
references
References 42 publications
4
70
1
Order By: Relevance
“…Our DsbC-assisted disulfide shuffling methodology is distinct from the traditional denaturant-based refolding protocols employed by other groups to produce CLR-RAMP ECD complexes. 17,27,37 We previously employed our methodology to produce several other class B GPCR ECDs with 3 disulfide bonds. [30][31][32][33][34] Here, the methodology was successful for proteins with up to 6 disulfide bonds, which suggests that it may be more broadly applicable to various disulfide bond-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Our DsbC-assisted disulfide shuffling methodology is distinct from the traditional denaturant-based refolding protocols employed by other groups to produce CLR-RAMP ECD complexes. 17,27,37 We previously employed our methodology to produce several other class B GPCR ECDs with 3 disulfide bonds. [30][31][32][33][34] Here, the methodology was successful for proteins with up to 6 disulfide bonds, which suggests that it may be more broadly applicable to various disulfide bond-containing proteins.…”
Section: Discussionmentioning
confidence: 99%
“…27 Our results disagreed with the 70 nM K D reported for the binding of AM to a noncovalent RAMP2 ECD:CLR ECD complex as measured by SPR. 17 The basis for this discrepancy is unclear, but it seems unlikely that the ECD complex binds AM with nM affinity because several other class B GPCR ECD-peptide pairs exhibit lM binding affinities. [30][31][32][33]35 Although we were unable to obtain reliable ITC data for the tethered AM receptor ECD fusion, our AlphaScreen results nonetheless suggested that the MBP tag and covalent tether did not significantly alter AM binding.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The protein was expressed in Escherichia coli BL21DE3pLys (1 mM IPTG, 37°C, 3 h) and purified as described elsewhere (27). In brief, RAMP2-ETD was produced in inclusion bodies.…”
Section: Mass Spectrometrymentioning
confidence: 99%